HIGH-PRESSURE BEHAVIOUR ALONG THE JADEITE NAALSI2O6-AEGIRINE NAFESI2O6 SOLID SOLUTION UP TO 10 GPA - Nestola F.; Boffa Ballaran T.; Liebske C.; Bruno M.; Tribaudino M. (My University, 2006)
The volume variation as a function of pressure along the jadeite-aegirine solid solution was determined at room temperature up to pressures between 6.5 and 9.7 GPa by single-crystal X-ray diffraction. The unit-cell volumes collected at room pressure for the different compositions indicate a slight deviation from linearity along the join. The pressure-volume data have been fitted using a third-order Birch-Murnaghan equation of state (BM3-EoS). The bulk modulus, KT0, varies from 134.0(7) GPa for pure jadeite to 116.1(5) GPa for pure aegirine. Its evolution with composition along the join is not linear and can be described by the following second order polynomial: KT0 = 116.2(5) + [0.25(3) × (mol%Jd)] - [0.0008(3) × (mol%Jd)2] The value of the first pressure derivative K′ is close to 4 for all the samples investigated and can be used in a BM3-EoS to determine the volume variations of these pyroxenes up to 7-10 GPa. Along the join the highest compressibility among the crystallographic directions is always observed along a, however, the compression along b is the most affected by compositional changes. The strain ellipsoid analysis indicates that the major compression occurs on the (0 1 0) plane along a direction at abou t 145° to the c axis (from c to a). The anisotropy of the compression increases with increasing the aegirine component, as confirmed by the analysis of both the axial compressibility and the strain tensor. © Springer-Verlag 2006.
Keywords: COMPRESSIBILITY; HIGH-PRESSURE; NA-PYROXENES; SINGLE-CRYSTAL; X-RAY DIFFRACTION